The impact of the Family Medicine Model on patient satisfaction in Turkey: panel analysis with province fixed effects - Sparkes, Susan Powers; Atun, Rifat A.; Bärnighausen, Till (PLOS ONE, 2019)
Background In this study, we aim to establish the impact of the introduction of the Family Medicine Model patient satisfaction in the Turkish health system. Methods We use data on data 69,028 primary health care (PHC) patients over the period 2010-2012. We estimate the impact of the Family Medicine Model in panel regressions with province fixed effects, exploiting the sequential introduction of this health systems transformation across Turkey's 81 provinces. We use principal component analysis to reduce the dimensionality of the data from the European Patients Evaluate General/Family Practice (EUROPEP) patient satisfaction survey, to focus on the fundamental dimensions of patient satisfaction and to decrease the need for multiple hypothesis testing. We identified two key principal components. The first captured primarily information on satisfaction with provider behavior and the second on satisfaction with the organization of care. We then use these two principal components as outcome variables in our panel analysis to estimate the causal impact of the introduction of the Family Medicine Model. Results The Family Medicine Model significantly improved patient satisfaction across a range of dimensions. The coefficient results showed a positive and statistically significant impact (p-values<0.05) of the Family Medicine Model on the outcome variables representing the satisfaction dimensions clinical behaviour and the organization of care even after controlling for calendar time fixed effects. Conclusions The introduction of the Family Medicine Model in Turkey, which was primarily aimed at achieving universal health coverage goals, substantially improved patient satisfaction. This study provides some of the first national-level evidence that the introduction of a Family Medicine Model can substantially improve patient satisfaction.